Czas i wieczność - Ogrodnik, Bogdan (Śląskie Studia Historyczno-Teologiczne, 1998)
1. The subject of this article is problem of connection between time and eternity. The solvation of this problem depends on a kind of ontology, on basis of which this problem is formulated. The most suitable ontology for this purpose is – in my opinion – Ingarden’s ontology of real objects. However this ontology must be in a few aspects modified and developed. 2. The first part of this article presents thesis which belong to mentioned ontology. Those thesis will be used in second part of this article, which is devote to connection between time and eternity. The third part contains brief discussion of selected philosophical and theological concepts similar to the proposal presented in previous parts. Thesis: 3. Eternity understood as eternal „now” is the principle of unity of worldprocess. In this sense eternity is transcendent respect to the world. 4. Every „now” of a real object participates in eternity. So eternity penetrate the world and in this manner eternity is immanent in the world.